Assessment of effect of nasal continuous positive pressure on laryngeal opening using fibre optic laryngoscopy. Issue 3 (1st May 1999) - Gaon, P; Lee, S; Hannan, S; Ingram, D; Milner, A D
Abstract : AIM: To assess the effect of nasal continuous positive airways pressure (CPAP) on the dimensions of the laryngeal opening. METHODS: Nine preterm infants who had previously received ventilatory support for respiratory distress syndrome (RDS) were studied. All were receiving nasal CPAP. The laryngeal opening was visualised using a fibre optic video camera system. The ratio of width to length of the opening was measured on and off CPAP. RESULTS: In eight of the infants the width: length ratio increased on CPAP; mean change for group +24.4% (95% CI +11.9 to +37.9). CONCLUSIONS: Nasal CPAP seems to dilate the larynx. This may explain the selective beneficial effects of CPAP on mixed and obstructive apnoea.